KECERDASAN INTERPERSONAL DALAM PEMBELAJARAN MUSIK UNTUK MENCIPTAKAN PEMBELAJARAN YANG HUMANIS - Hana Permata Heldisari (Universitas Singaperbangsa Karawang, 2020)
This paper discusses the importance of developing interpersonal intelligence through learning music to create humanistic learning. Through the mixed method research design with explanatory, this research uses qualitative i.e. observation and interviews to interpret the results of quantitative analysis obtained from the tests and question form. The population in this research is the entire learner’s grades 1-3 SD Negeri Banyuurip Purworejo totaled 107 and sample a number of 32 students. Research results through an analysis of the correlation of product moment to mention that the higher the musical ability of the higher intelligence anyway. Interpersonal intelligence necessary to create humanistic learning where students understand their environment and themselves through learning music that aims to foster a sense and sensibility on themselves and also the surrounding environment. Music learning experience gives the learners to develop the ability of its music that leads to acceptance of its sense of musical ability with regard to sensitivity, feeling and appreciation of music without having to play musical instruments skillfully.